Enantioselective Au(i)-catalyzed dearomatization of 1-naphthols with allenamides through Tethered Counterion-Directed Catalysis. Issue 82 (29th September 2021) - Yu, Yunliang; Zhang, Zhenhao; Voituriez, Arnaud; Rabasso, Nicolas; Frison, Gilles; Marinetti, Angela; Guinchard, Xavier
Abstract : The Tethered Counterion-Directed Catalysis approach has been applied to the enantioselective Au(i ) catalyzed dearomatizations of 1-naphthols with allenamides. Abstract : The Tethered Counterion-Directed Catalysis (TCDC) approach has been applied to the enantioselective Au(i ) catalyzed dearomatizations of 1-naphthols with allenamides. Stereocontrol is ensured by the intramolecular ion-pairing between the chiral gold-tethered phosphate and an iminium unit, that provides a rigid, well-defined chiral environment to the key electrophilic intermediate.